An analysis of Public Expenditure and Economic Growth, case of Ecuador period 2000-2022 - Gómez-Bermeo, Kevin (2023)
This article analyzes the relationship between government spending and Ecuadorian economic growth from the first quarter of 2000 to the fourth quarter of 2022. The objective of this study is to test two competing theories. On the one hand, Wagner's Law (1890) defends the idea that variations in public spending are caused by economic growth. And, on the other hand, the Keynesian hypothesis (1937) which postulates that economic growth is a product of government spending. With this objective, the total expenditure is considered, as well as the different types of expenditure, for which some tests are carried out, including the cointegration analysis applying the Engle and Granger methodology, the Zivot-Andrews test, the Johansen, among others. The main results show that the Keynesian hypothesis is not fulfilled between the years 2000 and 2020 and Wagner's law is fulfilled if the total government expenditure is considered, as well as when only the current expenditure of the Ecuadorian government is considered.